Mechanical, Thermal, and Morphological Behavior of Silicone Rubber during Accelerated Aging. Issue 16 (2nd November 2018) - Kashi, Sima; Varley, Russell; De Souza, Mandy; Al-Assafi, Salwan; Di Pietro, Adriano; de Lavigne, Christelle; Fox, Bronwyn
ABSTRACT: An accelerated aging study on silicone rubber exploring the effects of exposure to a functional oil (polyalkylene glycol) at elevated temperature (195°C) is reported in this paper. Variations in mechanical (tensile, tear, hardness) and thermal (conductivity, specific heat capacity) properties were monitored versus aging time while permanent deformation of the rubber was evaluated through creep and recovery measurements. Morphology and surface chemistry of the aged rubber were also investigated through scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy, respectively. Aging had a significant impact on the mechanical properties with the ultimate tensile strength and elongation at break decreasing from 7.4 MPa and 2250% in unaged samples to 1.5 MPa and 760% in 6-week aged samples, respectively. The tear strength and hardness exhibited an initial increase during the early stages of aging, followed by a decreasing trend. In contrast, the thermal properties did not change significantly and FTIR did not detect any changes in the surface chemistry of the rubber with aging. SEM however, provided evidence of an increase in brittle behavior from the morphology of the fractured surfaces. GRAPHICAL ABSTRACT: